OPTIMAL DESIGN OF MODIFIED SPUR GEARS BASED ON MINIMUM FLASH TEMPERATURE - YU DongYang; JIANG JinKe; SONG Qiang; FANG ZongDe (Jixie qiangdu)
Considering the installation error and tooth flank clearance of modified involute cylindrical gears influencing on load density,oil film thickness,and local friction coefficient.an optimum design method based on the minimum flash temperature was proposed.Applied TCA and LTCA to modification technology,the friction coefficient was determined according to the film thickness ratio under different lubricating condition,oil film thickness and loads on contact line were discretized,so discrete temperature according to the Blok flash temperature formula were got.used genetic algorithm to optimize the parameter of curve,and got the best deviation surface.the results shows that there are more uniform loads and flash temperature with modified gears,while the smallest is at engaging-in area due to the effect of curvature radius,besides the flash temperature has little changes in the single tooth meshing zone of spur gear.